The Influence of Product Quality, Brand Image, and Lifestyle on The Purchase Decision of Yamaha NMAX Motorcycles at Yamaha Mega Utama Motor Depok Dealers - Prasetya, Mufida Alfian; Hardini, Resti; Digdowiseiso, Kumba (Ridwan Institute, 2024)
The study investigates the influence of product quality, brand image, and lifestyle on the purchase decision of Yamaha Nmax motorcycles using primary data collected from a sample of one hundred users. Employing multiple linear regression and the SPSS program for analysis, the findings reveal positive effects between product quality (X1) and purchase decision (0.157), brand image (X2) and purchase decision (0.174), and lifestyle (X3) and purchase decision (0.609). The simultaneous impact of these variables is significant, with lifestyle demonstrating the most substantial effect (0.000). While these results offer valuable insights for Yamaha, future research could explore additional factors, and it's essential to consider potential limitations, such as respondent biases. The findings underscore the importance of enhancing product quality to positively influence purchase decisions and suggest avenues for further research and strategic development.